KETAATAN PEMUGARAN BANGUNAN HUNIAN CAGAR BUDAYA DI JALAN HOS COKROAMINOTO, MENTENG - Arya Abieta; maria immaculata ririk winandari (architecture department, Engineering faculty, Universitas Diponegoro, 2022)
Menteng is an elite residential area designed with Garden City Concept in the early 20th century. This area is a modern housing pioneer in Batavia and has been designated as a conservation area through the Governor's Decree in 1975 and is equipped with the conservation classification map of heritage buildings. Currently, there has been a change in the character of the Menteng area, especially on HOS Cokroaminoto Street. This study explored the compliance level of building and environmental conservation between 1975 and 2022. The quantitative method was used to obtain the compliance level of building and environmental conservation. Research variables consist of physical plots such as building massing, building-line, building height, roof shape, terraces and balconies, openings, building materials, ornament, as well as buildings function. The results showed that the buildings that complied with the conservation regulations were 37% or 36 of 97 plots with ten of them having the original form. The ownerships of the ten buildings are the original owner, government agency, or foreign government. Based on the function, only 28 of 36 plots that obeyed the regulations still retains its original function as a residence